Identification of High-Risk Pregnancies by Maternal Serum Alfa Fetoprotein - Ganesh Babu, T. Eswar; Mastan, S.A.; Sowjanya, M. Sai; Rajesh, G.; Harshitha, K.; Madhavi, A.; Haritha, U.; Sindhulekha, B.; Babu, P. Sivanarendra (International Journal of Applied Sciences and Biotechnology, 2020)
Alfa- Feto- protein (AFP) is a protein produced by the baby in the womb. The protein is normally found in the blood stream of the mother, which tends to be elevated or lowered in the blood of the women carrying babies with certain abnormalities it is an Albumin like glycoprotein with a molecular weight of 70,000 D. Is a formed in the yolk sac. Non differential liver cells and the fetal gastro- intestinal tract. Elevated MSAFP levels have also been associated with Chromosome abnormalities, Omphalocele and gastroschisis and rarely congenital, additionally elevated MS AFP levels have associated with an increased risk for adverse perinatal out comes including preeclampsia, premature labor, low birth weight, placental abruption and stillbirth. Int. J. Appl. Sci. Biotechnol. Vol 8(2): 231-234